Controversy in the Management of Cholangitis Secondary to Hydatid Daughter Cysts. Issue 4 (1991) - Davidson, Brian; Ezaki, T.; Habib, Nagy
Abstract : A 36 year old Cypriot woman, resident in the U.K. since the age of three years, presented with pyrexia, jaundice and upper abdominal pain. On ultrasound examination the biliary tree was dilated, contained sludge and a cystic lesion was present in the liver. An endoscopic cholangiogram showed multiple filling defects in the bile duct which were not felt to be removable endoscopically and a nasobiliary drain was therefore inserted. On resolution of the cholangitis with drainage and antibiotics a laparotomy was performed. The right lobe of the liver was largely replaced by a multiloculated cyst and the bile duct contained multiple hydatid daughter cysts. A right hepatectomy was performed with t-tube drainage of the evacuated bile duct. She made an uneventful recovery and has had no problems on subsequent follow up. Histology confirmed an intrabiliary rupture of a hydatid liver cyst. Cholangitis secondary to daughter cysts is a rare but recognised complication of hydatid liver cysts. Management of hydatid liver cysts by formal resection is controversial but may be preferable in this situation.